Correlation and Path Coefficient Analysis in Yield and Yield-Related Components of Black Cumin (Nigella Sativa L.) Accessions, at Jimma, Southwest Ethiopia - Zigyalew Gashaw; Wosene Gebreselassie; Girma Hailemichael (International Journal of Agronomy)
Many research works have been done on black cumin focusing on its nutritional and medicinal properties. But, there is inadequate information on the association of yield and yield-constituting traits of black cumin to improve its production. Therefore, correlation analysis was made on thirty-six black cumin accessions evaluated at Jimma in simple lattice design during 2016, to quantify the relationship between traits. The result of the analysis showed that seed yield ha−1 had positive and highly significant correlation with number of effective capsules (0.88), secondary branches (0.73), plant height (0.72), total branches (0.71), steam thickness (0.58), primary branches (0.52), tertiary branches (0.52), harvesting index (0.47), and biological yield (0.43). Path coefficient analysis revealed that harvesting index, biological yield, and number of effective capsules exerted high and favorable direct contribution to seed yield at phenotypic level, whereas harvesting index, biological yield, primary and tertiary branches, number of effective capsules, and stem thickness showed positive direct effect at genotypic level. The favorable direct effects of these traits on grain yield indicate that keeping other variables constant, improvement of these traits will increase black cumin yield. Therefore, these traits should be kept in mind in the future breeding program of black cumin.